PERBANDINGAN PENGGUNAAN PERANGKAP SEDERHANA DENGAN UMPAN MADU DAN GULA AREN DALAM UPAYA MENURUNKAN JUMLAH KEPADATAN KECOA - Erpina SM Nadeak; Ishaq Ishaq; Weni Enjelina Enjelina (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2016)
Cockroaches is diseases can be controled with any ways such as sanitary, biological,mechanical, and chemical. In general, chemical way more done by people such as spraying or fogging,because it is considered more practical. However, smoke containing insecticides can be spreadthroughout the room in the house to leave residues that are harmful to humans, so it is necessary to findother controls that are safer for the environment and humans.This study aims to determine the effectiveness of a simple trap by using bait honey and palmsugar. The type of research that is used in this study is True Experimental research design with posttestonly control group design. In this study insects used were cockroach, while the combination of bait is thebait used honey and palm sugar.the results showed that of the three traps with traps each containing different lures that first trapcontains a trapped cockroach bait honey with a percentage of 8.33%, while the second trap containingpalm sugar bait with a percentage of 1.67% and the third trap is used as a control a number of 0%. So ofthe three traps by using different lures most effective is favored by cockroaches bait traps containinghoney with a percentage 8:33 and averaged 4.The suggestions in this study are expected before selanjutya For researchers doing researchthink small first major large rooms used as small of a room can affect hasiil of research undertaken.